Safety and tolerability of flexible dosages of prolonged-release OROS methylphenidate in adults with attention-deficit/hyperactivity disorder - Jan K Buitelaar (Dove Medical Press, 2009)
Jan K Buitelaar1, J Antoni Ramos-Quiroga2, Miguel Casas2, J J Sandra Kooij3, Asko Niemelä4, Eric Konofal5, Joachim Dejonckheere6, Bradford H Challis7, Rossella Medori81Department of Psychiatry, University Medical Center, St. Radboud and Karakter Child and Adolescent Psychiatry University Center, Nijmegen, The Netherlands; 2Department of Psychiatry, Hospital Universitari Vall d’Hebron and Department of Psychiatry and Legal Medicine, Universitat Autònoma de Barcelona, Barcelona, Spain; 3PsyQ, Psycho-Medical Programs, Program Adult ADHD, Den Haag, The Netherlands; 4Oulu University Hospital, Department of Psychiatry, Oulu, Finland; 5Groupe Hospitalier Pitie-Salpetriere, Paris, France; 6SGS Life Sciences, Mechelen, Belgium; 7Johnson & Johnson Pharmaceutical Research and Development, Titusville, NJ, USA; 8Janssen-Cilag EMEA, Neuss, GermanyAbstract: The osmotic release oral system (OROS) methylphenidate formulation is a prolonged-release medication for the treatment of attention-deficit/hyperactivity disorder (ADHD) in children, adolescents, and adults. We conducted a seven-week open-label extension of a double-blind study to assess the safety and tolerability of OROS methylphenidate in a flexible dose regimen (18–90 mg daily) for the treatment of adults diagnosed with ADHD (N = 370). Medication was adjusted to optimize efficacy and tolerability for each patient. Adverse events, vital signs, and laboratory parameters were assessed. Most patients (337; 91%) completed the seven-week treatment and the final dispensed dose was 18 mg (8%), 36 mg (29%), 54 mg (34%), 72 mg (20%), or 90 mg (9%). Adverse events were reported in 253 (68%) patients and most were mild or moderate in severity; most frequently reported included headache (17%), decreased appetite (13%), and insomnia (11%). Adverse events were rarely serious (<1%; 2/370). Small mean increases in systolic and diastolic blood pressure (both 2.4 mmHg) and pulse (3.2 bpm) were observed. Body weight decreased slightly (-1.5 kg). The results provide additional support for the safety and tolerability of prolonged-release OROS methylphenidate in a flexible dose regimen (18–90 mg/day) for the treatment of adults with ADHD.Keywords: attention deficit hyperactivity disorder, ADHD, adult, methylphenidate, safety